Production of xylanolytic enzymes by Penicillium janczewskii - Fanchini Terrasan, Cesar Rafael [UNESP]; Temer, Beatriz [UNESP]; Teixeira Duarte, Marta Cristina; Carmona, Eleonora Cano [UNESP] (Elsevier B.V., 2010)
The production of extracellular xylanase, beta-xylosidase and alpha-L-arabinofuranosidase by the mesophilic fungus Penicillium janczewskii under submerged cultivation was investigated with different carbon sources. Optimization steps included studies of carbon source concentration, temperature of cultivation and initial pH of culture medium. The production of these enzymes was increased two times when cultures were supplemented with brewer's spent grain at 2% concentration, pH 6.0 and carried out at 25 degrees C. Under these optimized conditions were obtained xylanase activity of 15.19 U mL(-1) and 23.54 U mg prot(-1), beta-xylosidase activity of 0.16 U mL(-1) and 0.25 U mg prot(-1) and alpha-L-arabinofuranosidase activity of 0.67 U mL(-1) and 1.04 U mg prot(-1).Brewer's spent grain is a promising substrate for P. janczewskii growth and xylanolytic enzyme production, since it is the main by-product from the brewing industry, available in large amounts and at low-cost in many countries. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Xylanase; beta-Xylosidase; alpha-L-Arabinofuranosidase; Agroindustrial by-products; Penicillium janczewskii